2020
DOI: 10.1155/2020/4814515
|View full text |Cite
|
Sign up to set email alerts
|

The Temperature Evaluation of the Buried Hill Geothermal Reservoirs in the Jizhong Depression, Bohai Bay Basin, China

Abstract: The Jizhong Depression is located in the western Bohai Bay Basin, eastern China. The deep strata are mainly composed of carbonate buried hill, and the shallow strata are a mainly siliciclastic deposition. In the present work, the Na-K-Mg triangle diagram and geothermometers were used to investigate the geochemical characteristics of shallow groundwater and reservoir temperature features of three geothermal reservoirs in the depression, including the Ordovician, the Cambrian, and the Precambrian Wumishan Format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(32 reference statements)
0
0
0
Order By: Relevance
“…Thus far, the geothermal waters in China Xiong'an New Area have been extensively studied, including hydrogeological and geochemical characteristics, genesis, and geothermal resources [9][10][11][12][13][14][15][16]. However, research on the enrichment mechanism of lithium in the geothermal waters in the study area is very rare, and only the lithium concentrations in the geothermal waters have been reported [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the geothermal waters in China Xiong'an New Area have been extensively studied, including hydrogeological and geochemical characteristics, genesis, and geothermal resources [9][10][11][12][13][14][15][16]. However, research on the enrichment mechanism of lithium in the geothermal waters in the study area is very rare, and only the lithium concentrations in the geothermal waters have been reported [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The Moho's shallow depth facilitates the conduction of this deep mantle heat [16]. Dong et al (2020) used oil test temperature data to draw a section map of formation temperature and formation distribution at 3500 m, revealing that the temperature of the northwestern uplift area is lower than the eastern uplift area, and the temperature of the convex area of the depression is generally higher than the temperature of the depression at the same depth [17]. Miao et al (2022) observed that the heat of the deep carbonate geothermal reservoirs in the Jizhong Depression mainly comes from the deep mantle.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing environmental problems and shortage of energy, it has become a universal consensus to intensify the development of geothermal and other renewable energy sources [1,2]. China has about 16.7% of global geothermal resources, especially the medium-and low-temperature geothermal resources, which means that geothermal energy has great utilization potential [3].…”
Section: Introductionmentioning
confidence: 99%